Descriptive Memoir of the Ministry of Health as on 1-4-54 Government of India Cabinet Secretariat O and M Division - Planning Commission (Planning Commission, 1955)
The Programme on mass scale is yet to be introduced in Madras, Andhra , Bombay, Bilaspur, Kutch and Andaman-Nicobar. Up to the end of February J954 about 28 million pursues have been tuberculin tested and about 9 million vaccinated in the whole country.
Government of India Cabinet Secretariat O and M Division